2001
DOI: 10.1119/1.1374251
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity: Measurement of the dielectric susceptibility of strontium titanate at low temperatures

Abstract: A cryogenic experiment determining the dielectric susceptibility of the ferroelectric substance, strontium titanate, in the 90-to 300-K temperature range is described. Evidence is presented for a structural phase transition in strontium titanate at 110 K. The experiment is suitable for advanced students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…It is characterized by good mechanical strength, high thermal and chemical stability, low coefficient of thermal expansion, high melting temperature, large nonlinear optical coefficients and, large dielectric constant [1,2] which are responsible for their widespread applications in the manufacture of thermistors [3], multilayer capacitors [4], and electro-optical devices [5], electromechanical devices [6], dynamic random-access memory [7], and field-effect transistors [8]. Superconducting quantum interference device (SQUID) is fabricated using superconductor thin films developed on SrTiO 3 substarte [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by good mechanical strength, high thermal and chemical stability, low coefficient of thermal expansion, high melting temperature, large nonlinear optical coefficients and, large dielectric constant [1,2] which are responsible for their widespread applications in the manufacture of thermistors [3], multilayer capacitors [4], and electro-optical devices [5], electromechanical devices [6], dynamic random-access memory [7], and field-effect transistors [8]. Superconducting quantum interference device (SQUID) is fabricated using superconductor thin films developed on SrTiO 3 substarte [9].…”
Section: Introductionmentioning
confidence: 99%
“…None of the detailed studies of the dielectric behaviour of SrTiO 3 in the quantum paraelectric regimes have included this effect explicitly in their analyses. More recent studies of the dielectric susceptibility of SrTiO 3 between 90 and 300 K [41,43,44] found a deviation from classical Curie-Weiss behaviour at 105-110 K. Viana et al [43] made the connection between this anomaly and the ferroelastic phase transition, but argued that the mechanism was the onset and dynamics of ferroelastic twin walls.…”
Section: Coupling Between the Ferroelectric And Ferroelastic Modesmentioning
confidence: 99%
“…Isovalent impurities in BT ceramics do not significantly affect conductivity, but off-valent impurities are known to significantly affect ferroelectric behavior and conductivity. Although only few regions rich in Nb were detected by EDS, their influence on the micro-structural uniformity was negligible, as reported in reference [11]. Fig.…”
Section: Resultsmentioning
confidence: 59%